PROGRAM KEMITRAAN MASYARAKAT DALAM PENGOLAHAN LIMBAH PLASTIK MENJADI BAHAN BAKAR MINYAK DI DESA MINANGA TIMUR - Steve Supit; Priyono Priyono (Universitas Mataram, 2023)
The balance between the social and economic fields of rural communities is a goal of the Indonesian government, which is related to the development of human resources which then has an impact on increasing community income. This Community Partnership Program was conducted to the PKK group in East Minanga Village, Pusomaen Sub-District, Southeast Minahasa Regency. The background of this program is based on environmental problems in the form of plastic waste pollution and economic problems in the community that require creative business alternatives. As a non-biodegradable material, plastic waste that is generally generated from the consumption of drinks or food from the community is often piled up and clogs the drainage flow of the community, resulting in flooding. Therefore, the main objective of this program is to find solutions to handle plastic waste through the application of technology and improve community skills through making crafts from plastic waste. The method used is a community development approach where the community is directly involved during the program and involves the participation of the government and of course students from the Department of Mechanical Engineering and Civil Engineering at Politeknik Negeri Manado. From the results of the program, there was an increase in group skills in processing plastic waste into fuel oil with a production amount of 3-4 kg of PP and LDPE type plastic waste to produce approximately 8 liters of kerosene substitute fuel. In addition, the increase in group knowledge in processing plastic waste into handicrafts is an achievement that opens the emergence of new business groups that have an impact on increasing family income. It is hoped that the results of this program can make East Minanga Village a pilot village that encourages the dissemination of research technology to improve the quality and prosperity of people's lives.